Risk of Diabetes Mellitus and Level of Physical Activity Among Young Adults Affiliated to A Medical College in Chengalpattu District - N B, Swetha; Josephine Priya K; Manasa R; Manjula V (National Journal of Community Medicine, 2023)
Background: India is home to 77 million diabetics. Roughly 30% of overweight people have diabetes and 85% of diabetics are overweight. Young adults are especially prone to diabetes due to increased junk food consumption and sedentary lifestyle. Many young adults would be leading a life as diabetic if they are not educated about and screened for the risk factors. This will also allow us to timely strategize effective prevention therapies. Methods: This was a Cross sectional study conducted among 210 young adults aged between 18-35 years and are affiliated to a medical college in Chengalpattu. Two validated study tools were used: Indian diabetic risk score (IDRS) and International physical activity questionnaire (IPAQ). Frequency, Chi-square test, One Way ANOVA and correlation was used for analysis. Results: 36.7% were obese. 27.1% and 55.2% had high and moderate risk of Diabetes mellitus respectively. BMI showed statistically significant association with IDRS risk. 53.3% of study participants were physically inactive. Age and gender were significantly associated with physical activity and Total MET min/week. Negative correlation was seen between IDRS score and Total MET minutes/week. Conclusion: There is an urgent need to screen the young adults for risk of diabetes and thereby reduce the incidence. Indian youth are at high risk for diabetes, which calls for an urgent action plan through intensive efforts to promote lifestyle modifications.